2006
DOI: 10.1007/s10519-006-9090-7
|View full text |Cite
|
Sign up to set email alerts
|

Speech Sound Disorder Influenced by a Locus in 15q14 Region

Abstract: Despite a growing body of evidence indicating that speech sound disorder (SSD) has an underlying genetic etiology, researchers have not yet identified specific genes predisposing to this condition. The speech and language deficits associated with SSD are shared with several other disorders, including dyslexia, autism, Prader-Willi Syndrome (PWS), and Angelman's Syndrome (AS), raising the possibility of gene sharing. Furthermore, we previously demonstrated that dyslexia and SSD share genetic susceptibility loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 68 publications
2
43
1
Order By: Relevance
“…SSD phenotypes have shown linkage to three dyslexia candidate regions, DYX5 (chromosome 3p12) [Stein et al, 2004], DYX2 (6p22) and two regions on chromosome 15 that have been associated with dyslexia: 15q21 and 15q14 [Stein et al, 2006]. As with ADHD, confirmation that the two disorders may be caused by the same genes depends on finding the actual genes involved.…”
Section: Speech Sound Disorder and Dyslexiamentioning
confidence: 99%
“…SSD phenotypes have shown linkage to three dyslexia candidate regions, DYX5 (chromosome 3p12) [Stein et al, 2004], DYX2 (6p22) and two regions on chromosome 15 that have been associated with dyslexia: 15q21 and 15q14 [Stein et al, 2006]. As with ADHD, confirmation that the two disorders may be caused by the same genes depends on finding the actual genes involved.…”
Section: Speech Sound Disorder and Dyslexiamentioning
confidence: 99%
“…Recent molecular genetics analyses have heightened interest in the comorbidity of RD, ADHD, and SSD because all three disorders have shown linkage to the same genetic locus at 6p22 (Fisher and DeFries 2002;Smith et al 2005;Willcutt et al 2002). Additionally, several studies have identified loci that are pleiotropic for RD and ADHD (Bakker et al 2003;Gayan et al 2005;Loo et al 2004) and RD and SSD (Miscimarra et al 2007;Smith et al 2005;Stein et al 2004Stein et al , 2006. This preliminary evidence for shared genetic risk factors suggests that all three disorders may overlap phenotypically, to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have all been performed using families affected by speech-sound disorder (SSD), characterised by developmentally inappropriate errors in speech production and considered to be a phonological subtype of SLI (Stein et al 2004(Stein et al , 2006Smith et al 2005). The first study of SSD (Stein et al 2004) focussed upon a region of chromosome 3 previously implicated in dyslexia (DYX5 [MIM606896]).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for linkage was also found using the reading scores (P < 0.006). The same set of families were also used in an investigation of a region of chromosome 15q which is deleted in Prader-Willi and Angelman Syndromes and has been linked to both autism (AUTS4 [MIM209850]) and dyslexia (DYX1 [MIM127700]) (Stein et al 2006). The factor scores were not employed in this study, but instead an affected sib-pair analysis was performed using a binary affection status.…”
Section: Introductionmentioning
confidence: 99%